Migration, ethnicity and psychoses: evidence, models and future directions. Issue 3 (9th September 2019) - Morgan, Craig; Knowles, Gemma; Hutchinson, Gerard
Abstract : There is a large body of research reporting high rates of psychotic disorders among many migrant and minority ethnic groups, particularly in Northern Europe. In the context of increasing migration and consequent cultural diversity in many places worldwide, these findings are a major social and public health concern. In this paper, we take stock of the current state of the art, reviewing evidence on variations in rates of psychoses and putative explanations, including relevant theories and models. We discuss in particular: a) the wide variation in reported rates of psychotic disorders by ethnic group, and b) the evidence implicating social risks to explain this variation, at ecological and individual levels. We go on to set out our proposed socio‐developmental model, that posits greater exposure to systemic social risks over the life course, particularly those involving threat, hostility and violence, to explain high rates of psychoses in some migrant and minority ethnic groups. Based on this analysis, the challenge of addressing this social and public health issue needs to be met at multiple levels, including social policy, community initiatives, and mental health service reform.